Planning For The Terminal Cargo Area Requirements at Komodo International Airport Labuan Bajo - G Guritno; Wahyudono; Moh. Azhar; Gumay NizarSyach; Yose Rizal Fasya (Whoosh: Journal of Transportation and Logistic, 2026)
After the COVID-19 pandemic, cargo growth at Komodo Labuan Bajo International Airport shows a significant pattern of increase in cargo growth rates compared to before the COVID-19 pandemic. The increasing demand for cargo services certainly has an impact on the ability of Komodo Labuan Bajo International Airport to provide cargo services to the maximum extent possible. To overcome the pattern of cargo growth, which is expected to continue to increase, it is necessary to build a special terminal for cargo handling. The planning of cargo terminal development is carried out by considering the calculation and processing of data from 3 (three) dependent variables, namely population growth of West Manggarai Regency (X1), aircraft movements at Komodo International Airport (X2), and GRDP per capita of West Manggarai Regency (X3), and 1 (one) independent variable, namely cargo growth at Komodo International Airport (Y). The selected data will be processed with multiple linear regression, which then gives a coefficient value of 26.28490158 (X1), -112.2805486 (X2), 0.754461199 (X3), and a constant value of -10529364 (Y). the results of the constant and coefficient values will be processed to then produce cargo growth forecasts in the plan years. Projections on the amount of cargo growth in the plan years are determined in 2025 (short-term) with an estimated cargo size of 4,312,645 kg and the need for a cargo terminal area is 3240 m2, for 2035 (mid-term) with an estimated cargo size of 6,813,018 kg and the need for a cargo terminal area is 3620 m2, and for 2045 (long-term) with an estimated cargo size of 9,313,391 kg and for a cargo terminal area requirement of 3895 m2.